The measure of the rule - Barr, Robert, 1849-1912 (Literature of Canada poetry and prose in reprint., 1973)
Robert Barr has been almost completely overlooked by critics and anthologists of Canadian literature, in part because, although he was educated in Canada, he spent most of his life in the United States and England. However, since most of his serious novels are either set in Canada or have some Canadian connection, Barr deserves attention. The Measure of the Rule, originally published in 1907, is the nearest he came to writing an autobiographical novel. It concerns the Toronto Normal School and the experiences there in the 1870s of a young man who undoubtedly is Barr himself. In this novel, Barr is exorcising unhappy memories and is ironic, even bitter, about the school's quality of education, the rigid discipline observed by its staff and their indifference to their students, and the sexual segregation practiced. A number of men under whom Barr actually studied are vividly caricatured. As a realistic study of Ontario's only central teacher-training institution in the late nineteenth century, The Measure of the Rule will appeal both to those interested in Canadian fiction of that period and to those more concerned with the evolution of the system of education established by Egerton Ryerson. Also included with this reprint of the novel is an essay originally published in 1899 and entitled 'Literature in Canada.' In this essay, Barr elaborated upon his opinions of the school system and its quality of education.